Effects of Acetaminophen on the Reproductive Parameters and the Ameliorative Effects of Rutin and Mesenchymal Stem Cells in Male Rats - Elduob , Rabihah E. A.; Alshailabi , Eda M. A.; Efkeren , Samia M. (Scientific Journal of University of Benghazi, 2023)
The present study has been designed to evaluate the effects of acetaminophen on the reproductive parameters and the ameliorative effects of rutin and Mesenchymal stem cells in male rats. The rats were divided into two studies: firstly, twenty young male rats were used as a source of bone marrow-derived MSCs. Secondly, fifty adult male rats were divided into 5 groups: Control group (G1); rats were administrated of AAP (750 mg/kg b.w.) every 72h for 21 days, then left for 30 and 60 days without treatment (G2), rats were administrated of AAP for 21 days then treated with RT (25mg/kg b.w/d) for 30 and 60 days (G3), rats were administrated of AAP for 21 days then the rats were injected by BM-MSCs (1.5x 106 cells in 0.5 PBS) in the tail vein for 30 and 60 days (G4), and rats were administrated of AAP for 21 days then the rats were injected by BM-MSCs in the tail vein, then treated with RT for 30 and 60 days (G5). Administration of AAP produced a significant decrease in the mean value of the Te, LH, and FSH levels after 30 and 60 days as compared to the C groups. Whereas rats treated with RT and MSCs showed a significantly high increase in the mean values of these hormone levels after 30 and 60 days compared with the AAP group. In conclusion, this study demonstrated that RT and MSCs when treated in combination, are protected against the AAP-induced decrease in the hormone level of testicular.